BRINGING DEMOCRACY TO LIFE IN THE CLASSROOM: IMPLEMENTATION OF PKN IN FORMING STUDENTS' NATIONALIST ATTITUDES AT SDN 091482 KASINDIR - Surya Novalina Panjaitan; Dewa Bagus Sanjaya; I Nengah Suastika (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Civics education faces threats from globalization and moral decadence. This study aims to analyze the implementation of Civics as a democratic education at SDN 091482 Kasindir and its contribution to the formation of students' nationalist attitudes. Using a qualitative approach with a single case study design, data were collected through a literature review, participant observation (12 Civics meetings in grades 4, 5, and 6), and interviews with 3 teachers, the principal, and 15 students. Data analysis used the Miles & Huberman interactive model. The results show that the implementation of Civics as a democratic education is realized through three main practices: deliberative discussions on national issues, simulations of joint decision-making, and collaborative projects of patriotism. The nationalist attitudes formed include pride as Indonesian citizens, a willingness to prioritize common interests, participation in simple national defense activities: ceremonies, mutual cooperation, and respect for national symbols. The main obstacles are limited time and teachers' understanding. This study contributes to the development of a nationalism-based democratic education model in elementary schools.